2022
DOI: 10.1186/s13049-022-01043-z
|View full text |Cite
|
Sign up to set email alerts
|

How to evaluate first aid skills after training: a systematic review

Abstract: Background To be able to help and save lives, laypersons are recommended to undergo first aid trainings. The aim of this review was to explore the variety of the elements of the measuring systems to assess the effects of first aid trainings on different aspects of first aid skills including practical skills, knowledge, and emotional perspectives. Methods This systematic literature review used Scopus and PubMed databases and searched for studies pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…Resuscitation training manikins are widely used to assess the efficiency of BLS skills (CPR/AED). This finding agrees with Minna et al [ 25 ], who found that the most commonly first aid skills after first aid training were practical skills, specifically the ability to perform cardiopulmonary resuscitation (CPR) and use an automated external defibrillator. This assessment was based on several standardized measurements and was frequently performed with the assistance of a resuscitation manikin and an observer.…”
Section: Discussionsupporting
confidence: 91%
“…Resuscitation training manikins are widely used to assess the efficiency of BLS skills (CPR/AED). This finding agrees with Minna et al [ 25 ], who found that the most commonly first aid skills after first aid training were practical skills, specifically the ability to perform cardiopulmonary resuscitation (CPR) and use an automated external defibrillator. This assessment was based on several standardized measurements and was frequently performed with the assistance of a resuscitation manikin and an observer.…”
Section: Discussionsupporting
confidence: 91%
“…The current approach mainly relies on instructors' visual assessments [26]. They often provide a holistic evaluation by checklist, generalizing the overall compression postures throughout the entire process without specifying each compression [27,28]. Through the comparison of five sets of data within individuals, we found significant statistical differences, indicating that each performance varied over time during CPR operations for each person.…”
Section: Discussionmentioning
confidence: 96%
“…This involves maintaining the correct compression rate and depth, ensuring thoracic recoil, and minimizing interruptions and hyperventilation. However, traditional training methods have presented challenges, particularly for nonmedical personnel [ 52 , 53 ], in mastering these vital competencies. Previous studies [ 52 , 54 ] have noted that simulated scenarios and repetitive practice often fall short of achieving adequate compression depth and frequency.…”
Section: Discussionmentioning
confidence: 99%